The amazing generation : your guide to fun and freedom in a screen-filled world - Haidt, Jonathan; Price, Catherine, 1978- (Rocky Pond Books, an imprint of Penguin Random House LLC, 2025)
This book addresses the impact of smartphones and social media on children's and adolescents' development. Written for a young audience, it combines informational text with illustrations, interactive activities, and personal reflections to encourage critical thinking about technology use. The authors present research-based perspectives, practical strategies, and first-person accounts from young adults, with the aim of helping readers develop habits that support well-being, independence, and personal growth in a digitally connected world.